Acute Pancreatitis: a late complication of dengue fever - A. P., Krithika; R., Ramya (International Journal of Contemporary Pediatrics, 2018)
Acute pancreatitis following viral infection is rare in children. Acute pancreatitis complicating viral infections has been described in the form of isolated case reports and small series. The commonly implicated viral infections have been coxsackie virus, hepatitis viruses, mumps, varicella, herpes simplex and cytomegalovirus. However, the etio- pathogenesis of pancreatitis in viral infections remains unclear. Also, the natural history of such pancreatitis has not been adequately studied. Here we present a case of acute pancreatitis following dengue infection.